Enzymes in Action: An Interactive Activity Designed to Highlight Positive Attributes of Extracellular Enzymes Synthesized by Microbes - Rachel M. C. Gillespie (American Society for Microbiology, 2014)

(untitled)
Microbial activities are widely exploited in the manufacture of valuable products. However, the many beneficial uses of microorganisms are often overshadowed by negative associations with disease and decay. This article describes an interactive activity aimed at school-aged children and members of the public, which introduces the concept of microbial enzymes and ultimately illustrates how the industrial uses of microbes have a positive impact on everyday life. Participants are guided through a simple chemical assay which allows them to use a hands-on approach to reveal bacterial enzymes at work. This activity is safe and economical to run and is suitable for use in both the classroom and external learning environments. Also included are supplemental educational resources to support the demonstration and suggestions for extensions to the activity described, which enable further exploration of the topic. This activity has been tested by more than 2000 people at public engagement events and has received much positive feedback.